Assessing the short-term outcomes of a piped water supply intervention in peri-urban Mozambique - Sequeira, A.; Admiraal, R.; Lário L. M. Herculano; Fraydson Conceição; Amélia Monguela; McHenry, M.; Halina T. Kobryn; Doepel, D. (Journal of Water, Sanitation and Hygiene for Development, 2019)
We use data collected as part of a baseline survey in 2012 and a survey 5 months post-intervention in 2014 to assess the short-term outcomes of a water supply intervention in Ribáuè, Mozambique. This intervention included the rehabilitation and expansion of a piped water system, revitalization of water committees, and creation of and capacity building for small-scale private water enterprises. Quantitative results suggest that the intervention led to an immediate significant increase in the use of piped water supply at the expense of unprotected wells and other non-revenue generating forms of unimproved water supply with more than a 2.5-fold increase in the usage of yard taps and water kiosks/standpipes and a 2-fold decrease in the use of unprotected wells. Family water consumption also increased by approximately 40 L/d, and the point-of-use treatment of water nearly tripled. Economic opportunities were generated for business and small enterprise owners due to the new water supply infrastructure, and piped water infrastructure had additional positive effects for both public and private sanitation facilities.